Challenging management of a corneal ulcer in a patient affected with rosacea - Bianchi, Eduardo; Davide, Tucci; marco, messina (Indian Journal of Case Reports, 2026)
This case report is intended to describe the challenging diagnostic process and management of a severe corneal ulcer in a patient with rosacea, initially misdiagnosed as herpetic keratitis, and subsequently considered as peripheral ulcerative keratitis (PUK), before reaching the correct diagnosis of rosacea-related marginal keratitis. Here, we present the case of an 80-year-old male presenting with long-standing ocular pain, tearing, and reduced vision in his left eye, unresponsive to intensive antiviral therapy. A complete ophthalmic and systemic workup was performed. Despite antiviral withdrawal, topical antibiotics, and a multilayer amniotic membrane transplantation, corneal thinning progressed to a descemetocele requiring a Gunderson flap. Reassessment of eyelids and skin revealed severe blepharitis and erythematotelangiectatic rosacea. Introduction of systemic doxycycline, topical steroids, topical antibiotics, and eyelid hygiene resulted in gradual improvement. Rosacea may cause severe, sight-threatening marginal keratitis that mimics herpetic keratitis or PUK. Careful evaluation of eyelids and periocular skin is essential. Early recognition of rosacea-related ocular disease is crucial in preventing progression of corneal damage.